Death and Desire in Car Crash Culture A Century of Romantic Futurisms - Vidal, Ricarda (Peter Lang AG, Internationaler Verlag der Wissenschaften, 2013)
Why are we so obsessed with cars? Shiny objects of desire, cars never cease to fascinate us. As symbols of freedom they return again and again in art and film, even if real freedom is sometimes only achieved in the final explosive crash - the climax of the sheer exhilaration of speed. 'Car crash culture' is a symptom of the twentieth century, Ricarda Vidal argues in this book, revealing that our love of the car and technology is caused by the continuing influence of turn-of-the-century ideas: the Futurist technological utopia and the Romantic return to nature and desire. Artists, writers and filmmakers have explored this troubled love affair with the automobile throughout the past century. The work of F. T. Marinetti, Giacomo Balla, Jack Kerouac, Andy Warhol, Jean-Luc Godard (Week End), Richard Sarafian (Vanishing Point), J. G. Ballard and David Cronenberg (Crash), Quentin Tarantino (Death Proof) and Sarah Lucas, among others, are shown to pursue these ideals, even as developments in modern cities and telecommunications continue to change the nature of speed and technology. While the first half of the twentieth century was concerned with the celebration of speed and acceleration, the car crash has now become an obsession of contemporary culture. Vidal concludes that our attraction to the car crash reflects the contemporary way of life in the West, which is defined by a Futurist technophilia, a Romantic longing for a higher meaning and an undeniable infatuation with the automobile.
Keywords: automobily; filmové rekvizity; automobiles; motion picture properties; car crash culture; car crash; elektronické knihy; electronic books